Exploring Gypsiness : Power, Exchange and Interdependence in a Transylvanian Village. - Engebrigtsen, Ada I. (Berghahn Books, 2007)
Romania has a larger Gypsy population than most other countries but little is known about the relationship between this group and the non-Gypsy Romanians around them. This book focuses on a group of Rom Gypsies living in a village in Transylvania and explores their social life and cosmology. Because Rom Gypsies are dependent on and define themselves in relation to the surrounding non-Gypsy populations, it is important to understand their day-to-day interactions with these neighbors, primarily peasants to whom they relate through extended barter. The author comes to the conclusion that, alth.